Study on Unsuspected Intrinsic Property of Melanin to Dissociate the Water Molecule, Implications in Pulmonary Biology - Herrera, Arturo Solís; Madrigal, Oscar Aguilera (Recent Research Advances in Biology Vol. 7, 2021)
Life originated in anoxia, but paradoxically many organisms came to depend upon oxygen for survival, independently evolving diverse respiratory systems for expel CO2 and acquiring oxygen to and from the environment, respectively. Thereby, Oxygen, a vital gas, and a lethal toxin, represents a trade-off with which all organisms have had a conflicted relationship. Oxygen is Essential to sustain life. Inhaled oxygen is absorbed by blood; dissolved oxygen reacts with food (present in the body as sugars) to produce energy and heat - metabolism. The study of oxygen movements in the tissues of the human body has been a matter of great interest ever since centuries. In the beginning of the past century, Dr. Christian Bohr and August Krogh’s work on respiratory physiology and capillary modelling using mathematical models to calculate molecular transport in microcirculation, trying to determine the negative impact of lack of oxygen transport to tissues. Supposedly, computer simulation allowed investigation of the dynamic and non-linear characteristics of the systems. But the results have been and are contradictory. In Germany, Dietrich Werner Lubbers (1917-2005) obtained several patents related to designs for the study of gases in tissues. The aim of Dietrich Lübbers’ research was to understand the entire pathway and regulation of oxygen transport from the blood into the mitochondria. Assessment of pO2 histograms on most organs, revealed a remarkable similarity under physiological conditions: a Gaussian distribution always with less than 5% of values less than 5mmHg. Other studies detected changes in the concentrations of oxy- ([HbO2]) deoxy- ([HHb]) and total haemoglobin ([HbT]=[HbO2]þ [HHb]) measured using near infrared spectroscopy (NIRS) [1]. It has been shown that diabetic rats have markedly decreased oxygen availability in the kidney, supposedly resulting from increased oxygen consumption [2].